PRODUCT INNOVATION TRAINING AND ASSISTANCE AS WELL ASPACKAGING FOR MICRO SMALL MEDIUM ENTERPRISES (MSMEs) TO INCREASE ENTREPRENEURSHIP SALES VOLUME IN SIMALUNGUN DISTRICT - Hendri Mayanta Tarigan; Nurmala; Yunardi (Universitas Efarina, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the driving force of the economy which is expected to improve people's welfare. Community creativity and the ability to utilize existing natural resources to guide ideas and creations are embodied in various MSME products. There are many MSMEs in Simalungun Regency with various MSME products. The purpose of this service program is to provide training and mentoring for MSMEs in Simalungun Regency through a virtual marketing strategy. This product and packaging innovation training and mentoring activity is expected to provide a good solution for MSMEs in Simalungun Regency Village.